Bāyazīd Roṣhān / Qiyām al-Dīn Khādim - Khādim, Qiyām al-Dīn, 1907 or 8- (Da Puṣhto Ṭolanay da khparawano, 1944)
Short biography of Pīr Roṣhān Bāyazīd Ansārī, fl. 1526-1572; includes a selection of poems from his works.